The Legal Construction of Land Bank Regulations to Realize Fair Management of State Land Assets in Indonesia - Fatimah AlZahra (Universitas Muhammadiyah Sidoarjo, 2017)
The fact that the amount of land is fixed while the need for physical development is increasing as the increase in population, leads to inevitable social conflict. Social conflict is caused by the conflict of interest between the government and the people. The people tend to be reluctant to let go of the land they owned for the development of infrastructure in public interest with the pretext that the price set by the government is too low. As an agency for which its primary task is to reserve land for the government that is obtained before the need arises, a land bank appears to be able to be considered one of the alternatives for land procurement without conflict that can be applied in Indonesia as a solution in overcoming the land crisis for development. Through the normative legal research method, this research aims to analyzes the land bank’s concept in finding a legal construction of land bank regulations to realize fair management of state land assets in Indonesia. The result of the research shows that the legal construction of regulations for a land bank as an effort to realize fair management of state land assets can be achieved with regulations equal to a law. Values of fairness, legal certainty, and legal usefulness in the organization of a land bank must be included in the legal and normative basis in the content of the proposed law.